Welcome to the metamodel: A reply to Pablé. Issue 1 (1st June 2019) - Craig, Robert T.
In 2017, Empedocles: European Journal for the Philosophy of Communication published an article by Adrian Pablé, an integrationist linguist, which considers the contribution that Roy Harris' theory of sign can make to communication theory in terms of the constitutive metamodel of communication theory. This brief response to that contribution concludes that integrationism is a useful but limited perspective and that its claim to exclusive validity should be rejected by communication theorists.